PERAN RESILIENSI DALAM MEMEDIASI HUBUNGAN ANTARA REGULASI EMOSI DENGAN DISTRES PSIKOLOGI PADA MAHASISWA PROGRAM STUDI KEDOKTERAN UNIVERSITAS SEBELAS MARET SURAKARTA - Rini Setyowati; Pratista Arya Satwika; Galuh Maitri Imantaka Dharma (Jurnal Psikohumanika, 2022)
This study aims to determine the role of resilience in mediating the relationship between emotional regulation and psychological distress in students of the Medical Study Program, Sebelas Maret University. The population of this study were all active students of the Sebelas Maret University Medical Study Program. The sample used is 90 people, taken using a proportionate stratified random sampling technique. Collecting data using a scale consisting of a psychological distress scale (α = 0.934), an emotion regulation scale (α = 0.907), and a resilience scale (α = 0.901). The results of the mediation analysis showed that there was no significant relationship between emotional regulation and psychological distress through resilience in students of the Medical Study Program, Sebelas Maret University (p=0.898>0.05). The estimated direct effect is greater than the effect of mediating resilience (-0.148>-0.0005). This is possible because there are other factors such as intrapersonal factors which consist of personality traits related to individual emotional tendencies and situational factors originating from situations that are felt to be harmful or offensive to individuals.